Debates en torno al sufragio y la ciudadanía de las mujeres en México - Cano, Gabriela (El Colegio de México, 2013)
The attitudes towards female suffrage are analized, that were manifest among the political and intellectuals elites during the first half of the Mexican 20th century. Defenders and also opponents to women’s vote used maternalist speeches that centered on motherhood as the axis of the citizens’ rights of women, as egalitarian discourses that put the accent on the equality of rights among individuals. The debate about the feminine suffrage, was at the same time, a discussion on possible gender’s identities at specific historical moments.